Targeting and regulatory mechanisms in chromosome-wide gene regulation using Drosophila melanogaster as a model organism - Figueiredo, Ana Margarida Adónis, 1986- (2012)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2010